2020
DOI: 10.1002/jia2.25529
|View full text |Cite
|
Sign up to set email alerts
|

Same‐day antiretroviral therapy is associated with increased loss to follow‐up in South African public health facilities: a prospective cohort study of patients diagnosed with HIV

Abstract: IntroductionSouth Africa introduced Universal Test and Treat in 2016 including antiretroviral therapy (ART) initiation on the same‐day as HIV diagnosis. Our study sought to evaluate the impact of same‐day ART initiation on loss to follow‐up (LTFU) and mortality comparing with patients who initiated ART after their HIV diagnosis.MethodsWe conducted a file review of patients with a HIV diagnosis and ART start date on file between September 2016 and May 2018 in six high HIV burden districts. Our primary outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
2
18
1
Order By: Relevance
“…At one end, ART clubs have high retention (90% retained up to 24 months post‐diagnosis) [ 13 , 14 ], however, with eligibility restricted to patients who first reliably engage in care at clinics [ 40 ], findings are indicative of a population that may have fewer retention challenges. At the other end, studies have identified higher rates of loss‐to‐follow‐up among patients linked to ART on the day of diagnosis, with such patients being lost on average within 55 days [ 41 ]. This finding is likely due to same‐day initiation policies improving linkage outcomes most strongly among those with substantial engagement challenges, who are then quickly lost.…”
Section: Discussionmentioning
confidence: 99%
“…At one end, ART clubs have high retention (90% retained up to 24 months post‐diagnosis) [ 13 , 14 ], however, with eligibility restricted to patients who first reliably engage in care at clinics [ 40 ], findings are indicative of a population that may have fewer retention challenges. At the other end, studies have identified higher rates of loss‐to‐follow‐up among patients linked to ART on the day of diagnosis, with such patients being lost on average within 55 days [ 41 ]. This finding is likely due to same‐day initiation policies improving linkage outcomes most strongly among those with substantial engagement challenges, who are then quickly lost.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, questions remain on how determinants of attrition may be altered by the introduction of treat-all guidelines, particularly patient characteristics such as CD4 cell count and WHO clinical staging. Previously, correlates of attrition have been sameday ART initiation, young age, sex, and being unmarried [13,18,[21][22][23]. Facility-level factors have also been noted.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors concluded that pragmatic research is needed to validate the effects observed in trials when rapid ART initiation is implemented in health systems. In contrast to trials, recent observational studies in Southern Africa found that same-day ART initiation was associated with lower retention in care [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%